Grounding Ocean Ethics While Sharing Knowledge and Promoting Environmental Responsibility: Empowering Young Ambassadors as Agents of Change - Cappelletto, Margherita; Giuffredi, Rita; Kastanidi, Erasmia; Vassilopoulou, Vassiliki; L'Astorina, Alba (Frontiers in Marine Science, 2021)
Actions addressing youths and marine science for “ambassadorship” are increasingly implemented via dedicated programs at the European and global level within the relevant policy frameworks, as a way for fostering the exchange of knowledge and cross-fertilizing practices among the Countries and basins. These programs are conceived to address the future generations of scientists, entrepreneurs, policymakers, and citizens, and to promote the awareness and shared responsibility on the sustainable use of marine resources in an authentic and credible way, through the empowerment of young researchers and professionals, communicators, or activists. Thus, such ambassadors are well-positioned to act as agents of change, improving the dimension of Ocean Ethics related to inclusive governance, especially necessary for an equal, just, and sustainable management of multi-actor and transboundary socio-environmental contexts. Pivoting on the Young Ambassadors' Program developed in the framework of the BlueMed Research and Innovation (R&I) Initiative for blue jobs and growth in the Mediterranean area as case practice, the article aimed to propose some reflections about the long-term perspective of such experiences. Outlining an emerging physiognomy of the “One Ocean Ambassadors,” it discusses their potential to build the next generation of responsible scientists, citizens, and decision-makers and to embed ethical principles in research-based marine governance. In addition, it addresses process-related elements, such as balancing advocacy and ethics and reflecting on the role of science communication. To further consolidate this practice, this article finally seeks to incorporate the intercultural aspects to connect the local to the global dimension toward a sustainable and value-based ocean governance.